The anti-inflammatory vasostatin-2 attenuates atherosclerosis in ApoE-/- mice and inhibits monocyte/macrophage recruitment - Xiong, Weixin; Wang, Xiaoqun; Dai, Daopeng; Zhang, Bao; Lu, Lin; Tao, Rong (Thrombosis and Haemostasis, 2017)
We showed previously that reduced level of vasostatin-2 (VS-2) correlates to the presence and severity of coronary artery disease. In this study, we aimed to figure out the role of chromogranin A (CGA) derived VS-2 in the development of atherosclerosis and monocyte/macrophage recruitment. Apolipoprotein E-deficient (ApoE-/-) mice fed a high-fat diet exhibited attenuated lesion size by 65 % and 41 % in En face and aortic root Oil red O staining, MOMA-2 positive area by 64 %, respectively, in VS-2 treatment group compared with PBS group. Proinflammatory cytokines tumour necrosis factor-alpha (TNF-α), monocyte chemoattractant protein-1 (MCP-1) and vascular cell adhesion molecule-1 (VCAM-1) were all remarkably reduced in aortic tissues after VS-2 treatment. Mechanistically, in adhesion assay using intravital microscopy in vivo, VS-2 suppressed the number of leukocytes adhering to the wall of apoE-/- mice mesenteric arteries. In chemotactic assay, flow cytometry analysis of peritoneal lavage exudate from C57BL/6 mice showed VS-2 significantly decreased the recruiment number of inflammatory monocytes/macrophages in a thioglycollate-induced peritonitis model. Furthermore, fewer fluorescent latex beads labelled Ly-6Chi monocytes accumulated in aortic sinus lesions of apoE-/- mice after VS-2 treatment. In addition, according to the microarray of human monocyte/macrophage, we found VS-2 stimulation caused a dose-dependent decrease of Rac1 expression and inactivation of Pak1 in mice primary monocytes as well as THP-1 cells and inhibited MCP-1/CCL-5 induced transmigration in vitro. In conclusion, the Chromogranin A-derived VS-2 attenuates atherosclerosis in apoE-/- mice and, in addition to its anti-inflammatory property, also acts as an inhibitor in monocyte/macrophage recruitment.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Atherosclerosis; monocytes; chemotaxis; inflammation; vasostatin-2